Application of Monitoring Handy Talkie Usage as Support For Security Operation Based Android At Polda Gorontalo - Harun, Rusni; Manurapon, Reynaldi; D. Paemo, Nuranissa; Ismail, Abdul Rahman (Journal of Computer Science and Informatics Engineering, 2025)
Information Technology is developing rapidly and it has a significant impact on various aspects of life, including the government sector. The process of data collection that used Microsoft Excel software and paper filing have drawbacks such as difficult data collection, data loss due to natural factors, and it was difficulty in determining the condition of HTs. The purpose of this reseacrh was to designed an application of innovative monitoring HTs for security based Android. This application utilizes Android technology and HT devices to improve the effectiveness and coordination of security within the Information and Communication Technology Division of Regional Police in Gorontalo. The methodology of research used was Research and Development (R&D). The application was created using Java programming using Android Studio, PHP, and HTML. It allows Polda personnel to log in, view HT types and stock, borrow and return devices, and upload transaction receipts. The database used was MySQL. The modeling used Unified Modeling Language. This system utilizes whitebox and blackbox testing. As a sample, researchers tested the HT Borrowing flowchart, obtaining a region (R) value of 3, an Independent Path value of 3, and a Cyclometric Complexity (CC) value of 3. Test scenarios, including login, menu, HT type, and history displays, were successful, demonstrating that the system correctly authenticates users, manages HT data accurately, displays complete information, manages returns and validation appropriately, and handles usage securely